Imported case of measles in a university setting leading to an outbreak of measles in Edinburgh, Scotland from September to December 2016. Issue 6 (22nd March 2018) - Kirolos, A.; Waugh, C.; Templeton, K.; McCormick, D.; Othieno, R.; Willocks, L. J.; Stevenson, J.
Abstract: In September 2016, an imported case of measles in Edinburgh in a university student resulted in a further 17 confirmed cases during October and November 2016. All cases were genotype D8 and were associated with a virus strain most commonly seen in South East Asia. Twelve of the 18 cases were staff or students at a university in Edinburgh and 17 cases had incomplete or unknown measles mumps rubella (MMR) vaccination status. The public health response included mass follow-up of all identified contacts, widespread communications throughout universities in Edinburgh and prompt vaccination clinics at affected campuses. Imported cases of measles pose a significant risk to university student cohorts who may be undervaccinated, include a large number of international students and have a highly mobile population. Public health departments should work closely with universities to promote MMR uptake and put in place mass vaccination plans to prevent rapidly spreading measles outbreaks in higher educational settings in future.